Influence of particle sizes on homogenous and heterogeneous wood cement board properties made from acacia mangium / Azlan Seraila and Shaikh Abdul Karim Yamani Zakaria - Seraila, Azlan; Zakaria, Shaikh Abdul Karim Yamani (2015)
Wood-cement board (WCB) is a panel product that has the advantages of inorganic and organic materials. However, the main problems affecting the manufacture and use of WCB are the inhibitory effects of wood on the setting of cement and the high specific gravity of the final product. This paper examines the potential and the use of particle sizes and board layer to facilitate the production of a WCB from Acacia mangium. WCB were manufactured with wood/cement (w/w) ratio of 1:3, target density of 1300kg m3 and AI2 (S04)3 and Na2 Si03 content as chemical additives of 3.0%. Besides that, WCB also manufactured with the layer (homogenous and heterogeneous). The WCB were tested for static bending (MOR and MOE) properties in parallel (II) and perpendicular (T) directions; internal bond (IB), thickness swelling (TS) and water absorption (WA).